Motivation and Participation of EFL Students in the Implementation of Scientific Approach - Rifyal Mukarram; M. Basri Wello; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2018)
The aims of this study are: 1) to investigate the EFL students’ motivation in the implementation of the scientific approach (SA) and 2) to investigate the EFL students’ participation in the implementation of the scientific approach (SA). This investigation was under Classroom Action Research (CAR) and was done in two cycles consisted of four stages namely planning, acting, observing and reflecting. The subjects were the students of SMP Negeri 2 Sinjai Tengah in academic year 2016/2017. The data was collected through observation, questionnaires, and interview. While the results of CAR, both in the first and the second cycle shows that the students’ motivation and participation in the English learning process significantly improved by implementing SA. All students gave positive responses toward the implementation of SA in the English class. Of the two variables, participation variable is higher than the motivation variable. For learning motivation, students’ reaction toward the teacher’s responses and spirit of the students in carrying out their tasks were the most motivating factors of the students in learning. Meanwhile for the classroom participation, classroom embodied action and silent or non-oral participation were the most participation activities favored by students.